2013
DOI: 10.5130/ajceb.v13i1.3046
|View full text |Cite
|
Sign up to set email alerts
|

Textual complexity of standard conditions used in the construction industry

Abstract: Clearly written communication aids the understanding of construction contracts, resulting in less disputation. Past research, using opinion surveys rather than objective criteria, shows that construction contracts lack clarity and standard forms have become complex over time. The study outlined in this paper uses three objective measures of clarity developed by linguists to establish the readability of construction contracts. In addition, thirty industry professionals participated in a Cloze Test which measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…For example, FIDIC revised its standard form five times since its first publication in 1957. Rameezdeen and Rodrigo (2013) showed that clarity has continually improved in each of these new editions. Lack of clarity in contract documents can adversely affect the relationship between the client and the contractor and can even lead to disputes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, FIDIC revised its standard form five times since its first publication in 1957. Rameezdeen and Rodrigo (2013) showed that clarity has continually improved in each of these new editions. Lack of clarity in contract documents can adversely affect the relationship between the client and the contractor and can even lead to disputes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the improvements to a few clauses, more than 50% of the original and modified clauses are still at the 'very difficult' level of readability, which equates to requiring post-graduate study level to understand. Studies by Rameezdeen and Rodrigo (2013), Ali and Wilkinson (2010), Raj et al (2009) and Bunni (2003) show the majority of FIDIC contract conditions are very difficult to read. Modifications to contact conditions have not brought significant improvements on readability.…”
Section: Discussionmentioning
confidence: 99%
“…This also includes the textual complexity and unnecessary formality in contract wordings of some contract conditions (i.e. FIDIC, 1999 andNEC, 1993) that are very difficult to read, and require at least college-level reading skills to correctly interpret them (Rameezdeen and Rajapakse, 2007;Rameezdeen and Rodrigo, 2013).…”
Section: Propositionmentioning
confidence: 99%
“…It is important to emphasise here that lawyers and specialist surveyors are not the primary users of a contract; it is the project parties' ability to capture their meaning which is fundamental for contract performance (Rameezdeen and Rodrigo, 2013).…”
Section: Propositionmentioning
confidence: 99%
“…QSs position outside production has not only hampered their value addition to the project team, but has allowed inefficiencies (termed wastes in lean) in their roles and across the project spectrum. For instance, QSs are not the main users of a contract, however the complexity in which they interpret the onerous document encouraged opportunistic behaviours among parties that leads to severe disputes (Sarhan et al, 2014;Rameezdeen and Rodrigo, 2013).Similarly, how they apportion risk using disclaimer clauses attracts about 8-20% project cost as contingencies (Zaghloul and Hartman 2003). Thus, this creates more rigors that stifle collaboration with a persistent focus on individual party functions, that build more distance among the participants encouraging lots of adversaries (Eriksson, Nilsson and Atkin, 2008).…”
Section: How Qss Position Is Conflicting Collaborative Arrangement Inmentioning
confidence: 99%